Trajetórias venezuelanas: o processo de integração em Belo Horizonte - Miranda, Uiara Lopes (2020)
In recent years, the theme of forced migration and refuge has been reaching Brazil with greater intensity. The experience with the reception of Haitians, Syrians and, more recently, Venezuelans, has put pressure on brazilian institutions to respond quickly and in line with internal rules. With the migratory flow of Venezuelans, Brazil sought to institutionalize a response through “Acolhida Operation” or “Operation Welcome”, a federal government task force involving multiple actors, with a focus on emergency reception, shelter and interiorization (voluntary displacement to other brazilian states) of Venezuelans. Interiorization, which is taking center stage in “Acolhida Operation”, has delegated the task of protecting and welcoming Venezuelans to the cities, which also face their own challenges. In this research, we sought to carry out a qualitative analysis of the phenomenon of local integration of immigrants and refugees, through semi-structured interviews with Venezuelans living in Belo Horizonte, and also with actors who participated in the process. The analyzes of the collected reports were carried out based on structural, civil and socio-cultural aspects, dimensions captured in the literature that addresses the theme. It also sought to understand how policies and regulations developed globally and locally, for the protection of immigrants and refugees; and to show the responses to welcome, protect and integrate displaced persons in their host communities. With this, it is expected to contribute to the study of the theme in the Brazil, bringing subsidies for the development of public policies and for the clarification of the theme, to understand the Brazilian society itself, which also changes with the people who arrive. Brazil has a long historical path, in terms of migratory, discriminatory and protectionist policies, and this is reflected in an institutional lack of preparation to deal with the issue of migration. Institutional spaces are scarce and there are no adequate public policies that make possible some aspects of the local integration of immigrants and refugees, this role being then delegated to other institutions - such as religious and humanitarian aid. People or groups with limited rights and opportunities can integrate in different ways, which can lead to disadvantages and marginalization. Venezuelan displacement presents itself as a historic opportunity to expand the range of knowledge about Refuge in Brazil, presenting opportunities for future studies not covered in this research, such as the indigenous Refuge, the political dimension of the integration process and the articulation of federated and local entities that are still recent and need further study.